2015
DOI: 10.4103/1008-682x.135124
|View full text |Cite
|
Sign up to set email alerts
|

Male patients with terminal renal failure exhibit low serum levels of antimüllerian hormone

Abstract: Male reproductive function is impaired during end-stage renal disease (ESRD). Disturbance of the hypothalamic-pituitary-gonadal axis, and therefore the regulation of sex hormones, is one of the major causes. Our focus was to include antimüllerian hormone (AMH) and inhibin B concentrations. Twenty male patients on hemodialysis, median age 40 (26–48) years, were analyzed for follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin, sex hormone-binding globulin (SHBG), testosterone, estradiol, AMH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 33 publications
1
9
1
Order By: Relevance
“…During spermatogenesis, the Sertoli cell has a crucial role by supporting and nourishing developing sperm. We have previously shown that men on hemodialysis experience a substantial decrease in AMH levels compared with healthy fertile controls [3]. In this study, we observed a trend towards increasing levels of AMH at 12 months after transplantation; however, this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…During spermatogenesis, the Sertoli cell has a crucial role by supporting and nourishing developing sperm. We have previously shown that men on hemodialysis experience a substantial decrease in AMH levels compared with healthy fertile controls [3]. In this study, we observed a trend towards increasing levels of AMH at 12 months after transplantation; however, this was not statistically significant.…”
Section: Discussioncontrasting
confidence: 51%
“…Because approximately 40% of men receiving a kidney transplant are less than 50 years of age, reproductive function following transplantation is a major concern [6]. Kidney transplantation was reported to improve sexual function and sex hormone profiles [3, 7, 8]. Although some hormonal disturbances can be fully or partly restored, shortly after successful kidney transplantation, an improvement in semen parameters appears to be slow [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found no association between miR-155 and CRP in this CKD population, indicating that the elevated miR-155 levels were a response to a mechanism other than inflammation associated with CRP as a cause of impaired semen quality. We have recently reported major decreases in plasma levels of AMH, a marker of Sertoli cell function, in men with CKD [ 6 , 7 ]. To evaluate this in relation to fertility, we included assay of AMH levels in this study, and found an association between low AMH levels and a low percentage of motile sperm cells in the entire study population.…”
Section: Discussionmentioning
confidence: 99%
“…Deterioration of kidney function may also imply disturbances of the hypothalamic-pituitary-gonadal axis with increased levels of luteinizing hormone and follicle-stimulating hormone and decreased testosterone levels [ 3 , 4 , 5 ]. We have previously shown that anti-müllerian hormone (AMH), a marker of Sertoli cell function, is decreased in all men with CKD [ 6 ], being most pronounced in CKD 5 [ 7 ]. Low AMH levels have also been seen in subfertile men without renal disease [ 8 ] and in men with nonobstructive azoospermia [ 9 ].…”
Section: Introductionmentioning
confidence: 99%